Metabolic engineering of Mortierella alpina for arachidonic acid production with glycerol as carbon source. Issue 1 (December 2015) - Hao, Guangfei; Chen, Haiqin; Gu, Zhennan; Zhang, Hao; Chen, Wei; Chen, Yong
Abstract Background Although some microorganisms can convert glycerol into valuable products such as polyunsaturated fatty acids, the yields are relative low due primarily to an inefficient assimilation of glycerol.Mortierella alpina is an oleaginous fungus which preferentially uses glucose over glycerol as the carbon source for fatty acid synthesis. Results In the present study, we metabolically engineeredM. alpina to increase the utilization of glycerol. Glycerol kinase and glycerol-3-phosphate dehydrogenase control the first two steps of glycerol decomposition. GK overexpression increased the total fatty acid content by 35 %, whereas G3PD1, G3PD2 and G3PD3 had no significant effect. Overexpression of malic enzyme (ME1) but not glucose-6-phosphate dehydrogenase, 6-phosphogluconate dehydrogenase or isocitrate dehydrogenase significantly increased fatty acid content when glycerol was used as carbon source. Simultaneous overexpression of GK and ME1 enabledM. alpina to accumulate fatty acids efficiently, with a 44 % increase in fatty acid content (% of dry weight), a 57 % increase in glycerol to fatty acid yield (g/g glycerol) and an 81 % increase in fatty acid production (g/L culture). A repeated batch process was applied to relieve the inhibitory effect of raw glycerol on arachidonic acid synthesis, and under these conditions, the yield reached 52.2 ± 1.9 mg/g. Conclusions This study suggested that GK is a rate-limiting step in glycerol assimilation inM. alpina . Another restricting factor for fatty acid accumulation was the supply of cytosolic NADPH. We reported a bioengineering strategy by improving the upstream assimilation and NADPH supply, for oleaginous fungi to efficiently accumulate fatty acid with glycerol as carbon source.